Критерии оценки эффективности теплоутилизационных систем энергетических установок - Степанова, А. И. (Енергетика і автоматика, 2017)
UDC 621.036.7 EVALUATION CRITERIA OF EFFICIENCY OF POWER PLANTS HEAT RECOVERY А. Stepanovа At present stage of development of the economy modernization of municipal power system of Ukraine requires the development and implementation of efficient technologies, including heat recovery of exhaust gases of power plants technologies. The development of these technologies is only possible on the basis of today’s integrated approaches to the analysis of efficiency and optimal design of heat recovery equipment. Such approaches need to include the development of new com-plex criteria for evaluating the efficiency of heat recovery systems, which should have a high sensitivity to changes in certain parameters of the system and also serve as an optimization objective. This can be achieved by incorporating some exergy performance criteria that are highly sensitive to changes in operating and design parameters of a heat recovery system. Using the same criterion of efficiency as the optimization objective function or the use of multi-criteria optimization allows more deeply study the work of a heat recovery system and appreciate its excellence with various parties. At present, the efficiency of heat recovery systems is estimated by a number of criteria, which involve mainly only one of the approaches to their construction: thermodynamic, Thermal Engineering, Technology, exergy, economic. The classification of the main criteria by which is currently estimated efficiency heat recovery power plant systems. Classification criteria of efficiency and the analysis carried out on the basis of the approaches to their construction: thermodynamic, heat engineering, technological, exergetic, economic. A comprehensive approach, which allows the analysis of the efficiency of heat recovery equipment to consider together several different aspects: namely, thermodynamic, thermal and technological. On the basis of this approach proposed by heat and exergy Exergy Technology performance criteria. In addition to these criteria, to assess the effectiveness and optimization gas counterflow heat recovery units offered quite intuitive and easy to use exergy efficiency criterion. These criteria are used to assess the effectiveness of heat recovery systems, power plants, as well as the optimization objective functions for solving optimization problems with a view to optimal design of heat recovery equipment. For heat recovery systems, boilers and glass furnaces, including boilers and heat exchanger Air heating, a comparative analysis of the sensitivity of various performance criteria to changes in operating and structural parameters of heat recovery systems. Comparative sensitivity analysis was performed on the basis of the proposed response factor.